A STUDY OF ORGANISATIONAL DECISIONMAKING PROCESS AMONG MIDDLE LEVEL FEMALE ENTREPRENEURS IN IBADAN METROPOLIS OYO STATE - Abiona, Adekeye; Alese, Oluwatoyin Dorcas (European Scientific Journal, ESJ, 2015)
The study investigated the decision-making style of female entrepreneurs (managers /directors of restaurants/event planning centres, home lessons / adult education centres, cyber café and informal daily money collectors). The research was carried out in Ibadan North Local Government Area, Oyo State, Nigeria. It observed that Nigeria is undergoing fundamental changes in all spheres where women are increasingly becoming self –employed, owners and managers of enterprises. Also, the decisionmaking style of this sector is different from that of the formal sector. The study thus provided answers to the following research questions: (i) how relevant is networking to the process of female entrepreneurs’ participation in organisational decision-making? (ii) of what significance is mentoring to the participation of female entrepreneurs in organisational decision-making? and (iii) to what extent would a peaceful home and spousal understanding influence female entrepreneurs’ career? Findings revealed among others, that 20(90.9%) of the female entrepreneurs totally utilised the indices of transformative style of decision-making while only 2(9.1%) did not. Transformative style was found to enhance decent work in the organisations. It was therefore, recommended among others that both public and private organisations should inculcate the ethics of decent work.